Confidence level and self-efficacy beliefs of mathematics teachers: evidence from Sarawak / Nor Hazizah Julaihi - Julaihi, Nor Hazizah (Universiti Teknologi MARA Cawangan Sarawak, 2019)
The purpose of this paper is to examine the confidence level and selfefficacy beliefs of Mathematics teachers, particularly in Kuching and Samarahan, using the instrument adapted from two reliable questionnaires: Trend in International Mathematics and Sciences Study (TIMSS) and Teachers’ Sense of Teaching Mathematics Efficacy Scale (TSES). The respondents consisted of 49 teachers from both primary and secondary schools. The analysis reported that teachers have shown practically high confidence level in teaching mathematics and they closely agreed on their beliefs about their own teaching mathematics efficacy. Further analysis indicated that the mean scores of confidence level and self-efficacy beliefs for the female teachers were slightly higher than the male teachers. Analysis also reported that there were no significant differences in mean scores between teachers’ confidence level and selfefficacy beliefs across gender, highest education attained and years of mathematics teaching. The correlations analysis saw a significant positive strong relationship between teachers’ confidence level and self-efficacy beliefs. These findings provided some evidences to the existing pool of knowledge about teaching efficacy beliefs as well as some distinct and new insights relating to efficacy issues